Fieldbus: technology application in a Co-60 sterilization plant - Karam, D. (2000)
Process instrumentation was made by pressure signals in the 1940s. In the 1960s, 4-20 mA analogue signals were introduced. The development of digital processors in the 1970s sparked the use of computers to monitor and control instruments from a central point. In the 1980s smart sensors were developed and implemented in digital control, microprocessor environments. Fieldbus is a generic-term that describes a new digital communications network. The network is a digital, bi-directional, multidrop, serial-bus, and communications network used to link isolated field devices, such as controllers, transducers, actuators and sensors. Fieldbus technology may improve quality, reduce costs and increase efficiency because information is transmitted digitally without analog to digital or digital to analog converters,which also minimizes hardware errors. Fieldbus communication is based on two-wire communication, interconnecting all the components in the system. This paper introduces Fieldbus technology in a Co-60 sterilization plant. (C) 2000 Elsevier Science Ltd. All rights reserved.